Preparation of nano-iron loaded cassava fibre composite material for hexavalent chromium removal - Shi, Haobin; Zhang, Wenbin; Chen, Feng; Shi, Qingsheng; Chen, Fei; Fu, Li; Zhao, Shichao (Penerbit Universiti Kebangsaan Malaysia, 2021)
Waste cassava fiber and tea polyphenols were used as carrier materials and reducing agents, respectively, to prepare nano-iron loaded cassava fiber composite (CF-FeNPs). This work investigated the factors affecting the removal of Cr(Ⅵ) by CF-FeNPs under different environmental conditions and the removal mechanism. The SEM characterization results show that as the initial Fe2+ concentration increases, the amount of nano-iron on the surface of the composite material increases. The results show that the increases of the initial Fe2+ content and dosage of CF-FeNPss can enhance the removal rate. Meanwhile, the decrease of the initial concentration of Cr(Ⅵ) solution and pH also beneficial for the removal performance. When pH=2.0 and the initial concentration of Cr(Ⅵ) is 10 mg/L, the removal rate of hexavalent chromium by CF-FeNPs can reach 81.4% within 2 h. The reaction conforms to the pseudo first-order kinetic model. The results of this study can provide technical reference for the remediation and treatment of Cr(VI)-containing wastewater.